English vowels - Azura Fazira; Dinda Gustiana; Yani Lubis (Jurnal Pendidikan dan Sastra Inggris, 2023)
Vowels in English are pronounced with the mouth open, they can be sung. Also, vowels in English can be long vowels and short short vowels. The number of short vowels is seven long: five diphthongs and eight diphthongs. Diphthongs: Combinations of two vowels in a syllable. In English it is very important to respect the abbreviations and the length of the vowels, as the length of a sound can depend on the meaning of the word. For example: boat - sheep The first word of the sound i is short, and in the second vowel combination it is a sound that I owe only i. Translation of the first word - ship and the second - sheep. English short vowel – truncated stressed vowel. Vowel length in English or monophthong. They recite a fixed articulation. The first diphthong resonates, creating a surprising syllable. And the second - just a quick point. English has short and long vowels. There are 6 short vowels, some say 7, including the sound schwa [ə], as in "go, still, cinema, etc.". The six short vowels are [ʌ], [æ], [e], [ɪ ] , [ɒ] and [ʊ] with examples /cup/, /black/, /yes/, /sit/, /rock/ and /pull/ each has 5, namely H. [u:], [i: ] , [ɑ:], [ɔ:] and [ɜ:] with examples of each word: /food/, /look/, /dark/,/call/ and /wallet.